2020
DOI: 10.1038/s41598-020-63994-6
|View full text |Cite
|
Sign up to set email alerts
|

Protecting the peri-domestic environment: the challenge for eliminating residual malaria

Abstract: Malaria transmission after universal access and use of malaria preventive services is known as residual malaria transmission. the concurrent spatial-temporal distributions of people and biting mosquitoes in malaria endemic villages determines where and when residual malaria transmission occurs. Understanding human and vector population behaviors and movements is a critical first step to prevent mosquito bites to eliminate residual malaria transmission. This study identified where people in the Solomon Islands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…where and when residual transmission is expected to occur. Numerous studies have used this model in Africa [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. However until now, only one of these studies has reported exposure estimates for sites located in Burkina Faso [18].…”
Section: Introductionmentioning
confidence: 99%
“…where and when residual transmission is expected to occur. Numerous studies have used this model in Africa [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. However until now, only one of these studies has reported exposure estimates for sites located in Burkina Faso [18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work demonstrated that the risk of being bitten by An. farauti , the dominant malaria vector, occurs early in the evening and pre-dominantly in the peri-domestic areas of house verandas and kitchens [ 39 ]. Hence, targeted IRS in these high risk structures could enhance malaria control in residual malaria foci [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study con rmed the locations of high malaria burden health zones in three of these provinces, de ning the residual malaria foci as small in size (e.g., individual villages), suggesting that strati ed control could target these foci effectively. Previous work demonstrated that the risk of being bitten by An farauti, the dominant malaria vector, occurs early in the evening and predominantly in the peri-domestic areas of house verandas and kitchens [37]. Hence, targeted IRS in these high risk structures could enhance malaria control in residual malaria foci [38].…”
Section: Discussionmentioning
confidence: 99%